2023
DOI: 10.21873/cgp.20369
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulated Circular RNAs in Colorectal Cancer: New Entities for Therapy and Tools for Identification of Therapeutic Targets

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY-NC-ND) 4.0 international license (https://creativecommons.org/licenses/by-nc-nd/4.0).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 223 publications
0
4
0
Order By: Relevance
“…Moreover, new genetic markers, such as microRNAs (miRs) and upregulated circular RNAs (circRNAs) seem to critically modify the TP53 expression levels in subsets of CRC patients (39). Two study groups reported a positive role of miR-887-3p in CRC by inhibiting cell proliferation and, in parallel, enhancing apoptotic rates due to wild type P53 activation, whereas miR-338-3p negatively affects the resistance rates to 5-fluorouracil (5-FU) in TP53 mutant CRC cases (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, new genetic markers, such as microRNAs (miRs) and upregulated circular RNAs (circRNAs) seem to critically modify the TP53 expression levels in subsets of CRC patients (39). Two study groups reported a positive role of miR-887-3p in CRC by inhibiting cell proliferation and, in parallel, enhancing apoptotic rates due to wild type P53 activation, whereas miR-338-3p negatively affects the resistance rates to 5-fluorouracil (5-FU) in TP53 mutant CRC cases (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic-based techniques have speeded up the identification of HCC-related circ RNAs (205)(206)(207), such as circMRD27 which mediates resistance to levantinib (208). Previously we have reviewed the role of circular RNAs in breast cancer (209,210), esophageal squamous cell carcinoma (211) and colorectal cancer (212). We have extended this work to HCC and identified circRNAs which promote growth of HCC in preclinical in vivo models by sponging miRs.…”
Section: Discussionmentioning
confidence: 99%
“…These issues are not discussed in further details in this review. Among the issues are pharmacokinetic CANCER GENOMICS & PROTEOMICS 21: 213-237 (2024) and pharmacodynamic aspects of the corresponding agents, immunogenicity, specificity, and delivery (15)(16)(17). The optimization process depends on the specific approach and the clinical scenario to be pursued.…”
Section: Technical Issuesmentioning
confidence: 99%
“…Physiologically, circRNAs are involved in a plethora of cellular functions (13). In cancer, circRNAs can exert oncogenic as well as tumor-suppressive functions modulating proliferation, angiogenesis, migration, and metastasis (14)(15)(16)(17). In addition, circRNAs can act as scaffolds or sponges for proteins, regulate transcription, interact with RNAs, modulate translation and, in some cases, they can encode proteins (18).…”
mentioning
confidence: 99%